Collaborative inclusion in South African restaurants: a case study on disability and accessibility - Mailovich, Annami (Graduate School of Business (GSB), 2025)
The study explores social inclusion barriers faced by people with disabilities in the hospitality industry and solutions to promote inclusion. Moreover, the study draws attention to an industry where exclusionary practices typically deprive people with disabilities of full participation in social activities and contributes to the literature on collaboration in design thinking. Using design thinking as a collaborative and inclusive innovation process between disabled and nondisabled participants in a two-day workshop, it describes the co-creation of solutions to overcome information barriers for disabled restaurantgoers. Removing these barriers equips disabled restaurant patrons with the information needed to make informed decisions to partake in social settings where physical barriers are commonplace. This qualitative study employed a single instrumental case study design, gathering data through interviews and observations and is analysed using Braun and Clarke's six-step framework. The findings are presented as three themes: First, inclusivity creates a welcoming setting in design thinking workshops by coupling accessibility with diversity. Second, resilience is critical in overcoming collaboration barriers and normalising accessibility among disabled and nondisabled participants. Third, synergy, forged by collaboration and efficient communication, shows the impact of collaborative efforts in fostering inclusivity and, ultimately, achieving social inclusion. Ethical considerations prioritised participant autonomy through transparent communication and incorporated their views in the development of the study through exploratory conversations. Based on these findings, this study contributes practical guidelines to improve accessibility innovations practitioners and organisations serving people with disabilities could apply.